Lobster Yield Dynamics in a Warming Ocean: A Generalized Linear Modeling Case Study in Prince Edward Island, Canada - Manzura Khan; Xiuquan Wang; Krishna Kumar Thakur; Ryan Guild; Rana Ali Nawaz; Muhammad Awais (Foods)
The lobster fishery is the third largest industry in Prince Edward Island (PEI), Atlantic Canada. Rising water temperatures due to global warming are impacting the successful completion of the lobster life cycle, which is heavily dependent on water temperature. This study investigated the relationship between lobster landings and sea surface temperature (SST) in PEI. Using Generalized Linear Models (GLM), we identified a significant correlation between annual historical lobster landings and monthly sea surface temperatures (SST) in the waters around PEI from 1990 to 2021. Considering the 5–8 year maturation period of lobsters, we applied a lagged SST structure over an 8-year period and used a Generalized Linear Model (GLM) to evaluate the relationship between historical SST and lobster landings. Our findings suggest that historical increases in SST are correlated with changes in lobster landings. Given the known sensitivities of lobster life cycles (i.e., spawning, larval development) and behavior (i.e., mating) to high ambient water temperature, our study also offers important insights for future fishery management under anticipated climate change scenarios.